(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
During the period of State Terrorism in Argentina, women held in clandestine detention centers had specific experiences linked to sexual violence. After their captivity, survivors suffered the invisibility of these practices in investigations, in various narratives and, until very recently, in reparatory policies. This work, based on the analysis of testimonies, aims to examine women’s experien- ces in Argentine clandestine detention centers from a gender perspective. The study pays particular attention to the possibilities that survivors had to narrate their experiences and to be listened in different spheres and scenes from the first complaints filed during the dictatorship, in Argentina and abroad, to the present. We will focus on the analysis of the changes in social frames for listening and what causes them.